2013
DOI: 10.1097/ta.0b013e3182877fed
|View full text |Cite
|
Sign up to set email alerts
|

Repeat head computed tomography after minimal brain injury identifies the need for craniotomy in the absence of neurologic change

Abstract: Care management study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 15 publications
1
36
1
Order By: Relevance
“…Few studies have shown that routine repeat head CT is beneficial. 7,14,15,18 In a study by Park et al 7 in adult patients with GCS scores > 7, it was reported that 37% (n = 22) underwent surgical intervention due to radiological progression without neurological decline. The mean time between the initial and repeat head CT scan reported was 10.10 ± 7.25 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have shown that routine repeat head CT is beneficial. 7,14,15,18 In a study by Park et al 7 in adult patients with GCS scores > 7, it was reported that 37% (n = 22) underwent surgical intervention due to radiological progression without neurological decline. The mean time between the initial and repeat head CT scan reported was 10.10 ± 7.25 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time between the initial and repeat head CT scan reported was 10.10 ± 7.25 hours. Thorson et al 15 reported that in patients requir- ing neurosurgical intervention, 32%-59% had no neurological decline before worsening of repeat CT. Based on their analysis, altered GCS score, Injury Severity Scale score, and the presence of mass effect were independently associated with worsening of repeat CT. In contrast, few studies have questioned the role of routine repeat CT in neurologically stable patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies with pediatric head trauma and serial CT, of the patients 9-16% showed epidural hemorrhage (EDH), 4.28-40% showed subdural hemorrhage (SDH), 1-57% showed intracranial hemorrhage (ICH), 6.04-64% showed subarachnoid hemorrhage (SAH), 8.5-38% showed contusion, 37.5% showed linear fracture, 7% showed depression fracture (10,20,21,22). Durham et al reported that repeated CT screening is suggested in children with high risk lesions with EDH, SDH, cerebral edema and ICH while this screening was emphasized to have limited advantages in patients with SAH, ICH and isolated head fractures unless there is deterioration in clinical situation of patients and the evaluation of risks in radiation exposure is necessary (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thorson and col leagues reported that repeat head CT after mTBI and positive first head CT revealed progression of injury in 30% of patients before clinical deterioration of neurologic symptoms helped in the early identif ication of patients requiring craniotomy. 74 An other study comprising 1019 consecutive TBI patients at a level I trauma center reported that worsening findings on the sched uled repeat head CT for patients with an abnormal first CT more likely result in neurosurgical intervention compared with a sta ble scheduled second head CT. 59 On the other hand, some investigators have reported that routine repeat head CT is not indicated for mTBI patients, even those whose initial head CT was positive for mTBI. Three factors independently predicted a worse repeat head CT: age 65 years or older, Glasgow Coma Scale score lower than 15, and multiple traumatic intracranial lesions noted on initial head CT. 75 Magnetic resonance imaging (MRI) is not commonly used in the acute management of TBIs; however, MRI has critical value in the diagnosis and management of injuries that cannot be suf ficiently evaluated by CT, such as diffuse axonal injuries.…”
Section: Use Of Imaging In the Manage Ment Of Traumatic Brain Injurymentioning
confidence: 99%